An example of host plant expansion of host-specialized Aphis gossypii Glover in the field - Hu, Dao-Wu; Zhang, Shuai; Luo, Jun-Yu; Lü, Li-Min; Cui, Jin-Jie; Zhang, Xiao (PLOS ONE, 2017)
The host plant expansion of host-specialized Aphis gossypii (Glover) has been well studied in the laboratory; however, this phenomenon is poorly understood in the field. Here, we provide a series of laboratory and field experiments to assess the role of zucchini in the host plant expansion of cotton-specialized aphids. We observed that cotton-specialized aphids possessed the ability to expand on a new host plant (cucumber), with individuals first recorded on June 12 and consequently increasing exponentially in number in a field cage. A bioassay experiment showed that aphids from both cotton and cucumber preferred their natal host, but clones from zucchini have a stronger preference for cucumber than cotton or zucchini. A total of 1512 individuals were collected from a cotton field (mixed cotton and cucurbit plot), cotton farmland (cotton alone) and a field cage and sequenced to identify their biotypes. The results for apterous individuals from the cotton field showed that more cucurbit-specialized biotypes occurred on cucumber and more cotton-specialized biotypes occurred on cotton and zucchini. A majority (> 97.0%) of aphids from both the field cage and cotton farmland were cotton-specialized individuals. Consequently, eliminating intermediate host plants may be an effective measure to suppress A. gossypii outbreaks, because cotton and cucumber are often grown together in fields and greenhouses.